A 15-day pilot biodiversity intervention with horses in a farm system leads to gut microbiome rewilding in 10 urban Italian children - Daniel Scicchitano; Lucia Foresto; Cédric C. Laczny; Nicoló Cinti; Rosalba Vitagliano; Rashi Halder; Gaja Morri; Silvia Turroni; Federica D'Amico; Giorgia Palladino; Jessica Fiori; Paul Wilmes; et al. (One Health)
To provide some glimpses on the possibility of shaping the human gut microbiome (GM) through probiotic exchange with natural ecosystems, here we explored the impact of 15 days of daily interaction with horses on the GM of 10 urban-living Italian children. Specifically, the children were in close contact with the horses in an “educational farm”, where they spent almost 10 h/day interacting with the animals. The children's GM was assessed before and after the horse interaction using metabarcoding sequencing and shotgun metagenomics, along with the horses' skin, oral and fecal microbiomes. Targeted metabolomic analysis for GM-produced beneficial metabolites (i.e., short-chain fatty acids) in the children's feces was also performed. Interaction with horses facilitated the acquisition of health-related traits in the children's GM, such as increased diversity, enhanced butyrate production and an increase in several health-promoting species considered to be next-generation probiotics. Among these, the butyrate producers Facecalibacterium prausnitzii and F. duncaniae and a species belonging to the order Christensenellales. Interaction with horses was also associated with increased proportions of Eggerthella lenta, Gordonibacter pamelae and G. urolithinfaciens, GM components known to play a role in the bioconversion of dietary plant polyphenols into beneficial metabolites. Notably, no increase in potentially harmful traits, including toxin genes, was observed. Overall, our pilot study provides some insights on the existence of possible health-promoting exchanges between children and horses microbiomes. It lays the groundwork for an implemented and more systematic enrollment effort to explore the full complexity of human GM rewilding through exchange with natural ecosystems, aligning with the One Health approach.